Copper-Catalyzed Twofold Silylmetalation of Alkynes - Yamagishi, Hiroki; Shimokawa, Jun; Yorimitsu, Hideki (Synlett, 2019)
The first twofold silylmetalation across a C≡C triple bond was achieved. In the presence of a catalytic amount of copper cyanide, diarylacetylenes were converted into 1,2-dimetalated 1,2-disilyl-1,2-diarylethanes on treatment with silylpotassium species generated in situ from disilane and t-BuOK. The dimetalated species were subsequently protonated to yield a series of 1,2-disilyl-1,2-diarylethanes.
Keywords: silylmetalation; disilane; copper catalysis; ate complex; disilyldiarylethanes